Reflection-based Whole-batch Discussion (RWD) as a Tool for Learning Proficiency Enhancement at Faculty of Medicine, Universiti Sultan Zainal Abidin in Malaysia: Toward Curriculum Development - HA, Uday Younis; SA, Marwan; MJ, Haitham; HAM, Rana Abdulrahman; AR, Nor Iza; S, Nordin (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Different approaches have been endeavoured by medical educationists to produce high[1]standard graduates from medical school, including collaborative group discussions and reflective practice (RP) assignments. The current study aimed to evaluate the outcome of teacher-led whole batch discussion following RP tasks given to the students. The overall teaching approach is referred to as “Reflection-based whole-batch discussion (RWD)”. MATERIALS AND METHODS: One hundred twenty-two medical students who attended the haematology course at the University Sultan Zainal Abidin were recruited into this study over 2 academic years. The first batch of students (n=61) was unexposed to the RWD intervention (RWD-unexposed) while the second batch from the following academic year (n=61) was exposed (RWD-exposed) to the intervention. Students adhered to the guidelines given by the instructor pertaining to the reflective practice (RP) before the sessions. A weekly RWD session was conducted where the instructor-led a dually interactive forum to discuss students’ mistakes and misunderstandings as reflected within their write-ups. Exam results from both RWD-exposed and the RWD[1]unexposed students were compared using the student t-test. RESULTS: The mean scores of students’ results were significantly higher among RWD-exposed students compared to RWD-unexposed students in their essay questions and objective structured practical exam questions (p<0.01). However, RWD-exposed students scored significantly lower than the RWD-unexposed < 0.01). However, RWD-exposed students scored significantly lower than the RWD-unexposed student’s group in multiple true and false (MTF) questions. CONCLUSION: Implementing RWD is a promising teaching strategy in improving the academic achievement of medical students especially in answering essay questions. MTF questions format may be an incompetent tool for evaluating the impacts of new teaching strategies and therefore medical educationists recommended efficient alternative assessment tools such as OBA and EMQ for the sake of curriculum development in medical institutes.